Perswazja, manipulacja, zabawa językiem – wybrane aspekty językowe czasopisma „Wróżka” - Sokół, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2010)
The article contains chosen language means which are responsible for manipulation and persuasion in magazine Fairy. Manipulation is usually presents in expressive, stylistic means, because they affect emotions of readers and create atmosphere of mysteriousness. Persuasion is achieved in those texts by quoting rich argumentation, referring to historical evidences and scientific knowledge. Focusing on reasons of interest in fortune-telling among people of the 21 century the magazine’s author shortly describes the evolution of divination. She presents also language differences in new and old texts related with magic.